Human Cathelicidin, LL-37 a potential antiviral therapeutic for Rift Valley Fever Virus in Egypt: Cathelicidin, LL-37 antiviral therapeutic for RVFV - Ahmed, Engy M.; Boseila, Abeer A.; Hanora, Amro S.; Solyman, Samar M. (Cellular and Molecular Biology, 2024)
Rift Valley Fever Virus (RVFV) is an arbovirus that circulates among animals and can be transmitted to humans. Mosquitoes are the primary vectors that allow RVFV to spread vertically and horizontally. Egypt was exposed to frequent outbreaks with devastating economic consequences. RVFV has a high incidence of worldwide dissemination and no specific vaccine or therapy. Linear Human Cathelicidin (LL-37), is a natural antimicrobial peptide with antiviral activity against numerous viruses. In addition to immunomodulatory effects, LL-37 directly influences viral encapsulation. This study aimed to evaluate the antiviral activity of LL-37 against RVFV in vitro. The post-entry and pre-incubation of LL-37 within Vero cells were assessed in the absence and presence of RVFV. LL-37 activity was assessed using a TCID50 endpoint test, qRT-PCR, and a western blot. When genomic RVFV was quantified, it resulted in a 48% direct inactivation of the viral envelope and a 36% reduction when the virus was pre-incubated with LL-37 before infection. LL-37 decreased viral infection by 75% and protected Vero cells against RVFV infection by 47% at a 1.25 µg/ml dosage. These findings imply that LL-37 exerts antiviral efficacy against RVFV by restricting virus entrance through direct disruption of the virus envelope and indirectly by triggering an immunological response. The effect of LL-37 is time-dependent. As a result, LL-37 may provide rapid and affordable therapies for RVFV infection in Egypt, both during outbreaks and as a preventive strategy.